Pengembangan Bahan Ajar IPS pada Materi Keragaman Suku Bangsa dan Budaya Dengan Menggunakan Metode Storytelling di Kelas IV SD - Elda Nabilla; Tiflatul Husna (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This study aims to produce social studies teaching materials that can attract students' attention to the subject of Ethnic and Cultural Diversity using the storytelling method in class IV SDS IT Zahra Asy Syifa. This research is a Research and Development (R&D) development study using the ADDIE development procedure which consists of 5 stages. The instrument used to collect data was a validation questionnaire given to several expert validators, namely the material expert validator, teaching material expert validator and teacher response. The total score obtained from the validation of teaching materials was 97.6 with the criteria of "Very Eligible", from the validation of teaching materials experts, namely 96.8 with the criteria of "Very Eligible" and from the teacher's response a score of 98 was obtained with the criteria of "Very Eligible". From the results of the implementation, it is known that the score of student learning outcomes before using the developed teaching materials, namely 71.08 with the criteria of "Decent" and after using the teaching materials the score of student learning outcomes, which is equal to 82.17 with the criteria of "Very Eligible". From these results it can be said that Social Studies teaching material on Ethnic and Cultural Diversity uses the storytelling method which was developed "Very Feasible" for use in the learning process.